Use of low intensity ultrasound in the Longissimus dorsi muscle from pigs with different genetic background - Ventanas S.; Ventanas J.; Ruiz J.; Bon J.; Benedito J. (5. International Symposium on the Mediterranean Pig, 2007)
In this work, the use of low-intensity ultrasound on the Longissimus dorsi muscle as an objective and non-destructive analytical technique to differentiate between raw meat from pure Iberian pigs (Ib) and from Iberian x Duroc (IbxD) crossbreed pigs, was studied. Measurements of ultrasonic velocity at different temperatures (0°C-25°C) were carried out. Ultrasonic velocity decreased with the temperature of the samples. The decrease was significantly higher in the pure Iberian batch than in the IbxD batch. Measurements of ultrasonic velocity in the Longissimus dorsi muscle from Ib were higher at low temperatures (0-10°C) and lower at temperatures over 10°C, than in those from IbxD pigs. Taking into consideration that the fatty acid composition of both batches were similar, this factor is unlikely to explain the differences on ultrasonic velocity between samples. However, Longissimus dorsi muscles from Ib pigs show higher fat content than those from IbxD pigs (12.832±0.937 vs 6.644±0.662), which involves a higher fat/water proportion in the former. Therefore, this fact might explain that, compared to the other batches, the ultrasonic velocity in samples from Ib was higher at low temperatures and lower at high temperatures. Moreover, the higher fat content in Ib batch could explain the intense decrease of ultrasonic velocity with temperature in this batch. In conclusion, this results show that the measurement of the ultrasonic velocity in the Longissimus dorsi muscle could be used to differentiate between raw Longissimus dorsi muscles from pure Iberian pigs and from Iberian x Duroc crossbreed pigs.
5. International Symposium on the Mediterranean Pig, 2004/09/16-19, Tarbes (France)